(untitled) (International Journal of Food and Nutritional Sciences, 2025)
This study examined the impact of psychological anxiety regulation techniques on dribbling control and shooting accuracy among university basketball players using a quasi-experimental design with 156 participants (78 males, 78 females) randomly allocated to progressive muscle relaxation, visualisation, controlled breathing, or control groups. The intervention lasted for eight weeks and comprised a baseline assessment, four weeks of training sessions twice a week with daily independent practice, and an evaluation after the intervention with a follow-up four weeks later. The Competitive State Anxiety Inventory-2 Revised and the Sport Anxiety Scale-2 were used to evaluate anxiety levels. Standardised dribbling obstacle courses and shooting procedures, such as free throws and three-point shots, were used to test performance. The results showed that all of the intervention groups had a big impact on both cognitive and somatic anxiety compared to the controls. The effect sizes were modest to high. The visualisation group showed better improvements in dribbling control, with 14.3% quicker completion times and 40.6% fewer mistakes. The progressive muscle relaxation group showed the most increases in free throw accuracy, with an 11.2 percentage point improvement. Controlled breathing improved three-point shooting accuracy by 8.8 percentage points. Regression studies showed that the decrease of cognitive anxiety was a predictor of improvements in dribbling skill, while the reduction of somatic anxiety emerged as the most significant predictor of enhancements in free throw performance. Qualitative interviews identified themes of increased performance confidence, heightened attentional concentration, and significant intervention acceptance, with adherence rates above 86% across all groups. Performance enhancements were sustained during the four-week follow-up, indicating persistent intervention effects. These results show that anxiety regulation techniques can greatly improve basketball-specific skills. The different patterns of effectiveness show that it’s important to match interventions to the specific performance demands and anxiety components for the best results in college athletes.